2021
DOI: 10.1002/lary.29376
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Outcomes of Juvenile Onset Recurrent Respiratory Papillomatosis with Pulmonary Involvement

Abstract: Objective To investigate the clinical characteristics and long‐term outcomes of juvenile onset recurrent respiratory papillomatosis (JORRP) with or without pulmonary involvement. Methods A group of patients with JORRP who had clinical course over an extended period of time (at least 5 years) in the Department of Otolaryngology Head and Neck Surgery, Beijing Tongren Hospital were included in this retrospective study. Lung/bronchus involvement was revealed by lung imaging. Data on mortality rate, frequency of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Since tracheotomy is the primary cause of tracheal involvement, we and others have previously reported that the tracheal involvement rate in patients with tracheotomy ranges from 73.5% to 80%. 24,25 The tracheal involvement rate was low in this study because all patients had primary disease and did not undergo tracheotomy. Distal airway involvement has been used as a marker of aggressive disease because lesions in the distal airway often indicate more severe disease.…”
Section: Discussionmentioning
confidence: 84%
“…Since tracheotomy is the primary cause of tracheal involvement, we and others have previously reported that the tracheal involvement rate in patients with tracheotomy ranges from 73.5% to 80%. 24,25 The tracheal involvement rate was low in this study because all patients had primary disease and did not undergo tracheotomy. Distal airway involvement has been used as a marker of aggressive disease because lesions in the distal airway often indicate more severe disease.…”
Section: Discussionmentioning
confidence: 84%
“…The majority of the studies (10; 90.9%) had a retrospective/observational study design. The quality assessment showed a high risk of bias in the majority of the studies (8/10, 80%) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], whereas only two had a moderate risk (2/10, 20%) [ 34 , 35 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were published between 1997 [ 30 ] and 2021 [ 25 , 34 ]. The recruitment period ranged from 1981 [ 30 ] to 2020 [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…20,21,[27][28][29] This study is clinically relevant: our results highlight the benefit of sustained oxygenation with THRIVE in allowing uninterrupted surgery, thereby reducing the overall procedure time, lessening the intraoperative repeated intubation frequency, and subsequently decreasing the lower airway spread risk since many children with JORRP must undergo multiple procedures throughout their childhood. [2][3][4] The prolonged apnea time without desaturation reduced the stress on both the trainee and supervisor, thus permitting an unrushed operation.…”
Section: Discussionmentioning
confidence: 99%
“…For those patients, repeated surgical interventions are required to maintain airway patency and function. To ensure the best surgical exposure for the resection of tumors in the posterior glottis and trachea [3][4][5] (Figure 1B), a tubeless airway is needed (Figure 1B), which poses a tremendous challenge to anesthetists. To date, there is no consensus on the optimal airway strategy for shared airway management.…”
mentioning
confidence: 99%